Meningkatkan Semangat Kelompok Wanita Tani melalui Pelatihan Moderen dan Bersyariah Demi Keberlangsungan Ekonomi Keluarga di Desa Wates Jaya - Aguriat Ramadhan , Muhamad; Husnaasri, Kholifatul; Malikurrahamat, Faridudin (ALIF: Sharia Economics Journal, 2024)
This paper discusses an initiative to boost the morale of a group of women farmers in Wates Jaya Village through training that combines modern and sharia approaches. The main objective of this research is to improve the economic sustainability of families through empowering farm women at the local level. The training held was modern in nature by integrating the latest technology in agricultural practices and household economic management. In addition, a Shariah approach was applied to ensure sustainability in accordance with local values. The training covered new skills, natural resource management, and the application of sharia principles in daily life. The research method involved the active participation of farm women's groups in the development of the training program, as well as continuous monitoring and evaluation. The results showed significant improvements in group spirit, increased agricultural productivity, and improved family finances. In addition, the application of sharia values has provided a strong moral foundation for their economic activities. This research provides insights into how a holistic approach combining modern and sharia aspects can positively impact the morale of women farmer groups and the economic sustainability of families at the village level. The findings can serve as a foundation for the development of similar programs in other areas with similar social and cultural contexts in agriculture.